SCIENTIFIC THEORY AND PHYSICAL BUILT ENVIRONMENT - Harsritanto, Bangun I.R. (architecture department, Engineering faculty, Universitas Diponegoro, 2022)
Architecture has been developed through centuries and brought some pearls of wisdom, knowledge, empirical aspects, and physical form into the world. The construction of architecture not only can be seen and touched as a building or built environment but also in mind as a way of thinking. This writing suggested a diversity of architectural aspects to the readers about tangible and intangible legacy